2017
DOI: 10.1128/aac.00064-17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Escherichia coli Isolates Carrying mcr-1 , fosA3 , and Extended-Spectrum-β-Lactamase Genes from Food Samples in China

Abstract: This study surveyed the prevalence of mcr-1 in extended-spectrum-␤-lactamase (ESBL)-producing Escherichia coli strains of food origin in China and identified strains that carried mcr-1, fosA3, and ESBL genes, which were carried in various plasmids. The mcr-1 and ESBL genes could be cotransferred by one or more types of plasmids. The presence of these multidrug-resistant E. coli strains in food products might pose a huge threat to public health.KEYWORDS mcr-1, fosA3, ESBL-producing E. coli, transmission, circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
2
17
0
2
Order By: Relevance
“…Until 2015, almost all reported polymyxin resistance mechanisms were coded on the chromosome and mediated by mutations in two component regulatory systems (PmrAB, PhoPQ), loss of lipopolysaccharide, or mgrB inactivation in the case of K. pneumoniae [10,11]. Importantly, a report by Liu et al in November 2015 described the emergence of a conjugative plasmid-mediated colistin resistance gene, mcr-1 , which encodes an enzyme (MCR-1) that belongs to the phosphoethanolamine transferase enzyme family and leads to altered bacterial lipid A in Enterobacteriaceae through modification of the phosphoethanolamine moiety [10-12]. Identification of mcr-1 as a plasmid-mediated resistance mechanism highlights its potential to act as a transmissible colistin resistance determinant.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2015, almost all reported polymyxin resistance mechanisms were coded on the chromosome and mediated by mutations in two component regulatory systems (PmrAB, PhoPQ), loss of lipopolysaccharide, or mgrB inactivation in the case of K. pneumoniae [10,11]. Importantly, a report by Liu et al in November 2015 described the emergence of a conjugative plasmid-mediated colistin resistance gene, mcr-1 , which encodes an enzyme (MCR-1) that belongs to the phosphoethanolamine transferase enzyme family and leads to altered bacterial lipid A in Enterobacteriaceae through modification of the phosphoethanolamine moiety [10-12]. Identification of mcr-1 as a plasmid-mediated resistance mechanism highlights its potential to act as a transmissible colistin resistance determinant.…”
Section: Introductionmentioning
confidence: 99%
“…The dissemination of mcr genes in gram-negative bacteria isolated from food-producing animals and from food in Asian countries (Kawanishi et al, 2016;Liu et al, 2017;Wu et al, 2018) was confirmed by the detection of E. coli and C. braakii with the mcr-1 gene in two samples of rabbit meat imported from China. The examined rabbit meat samples from Hungary and the Czechia did not contain bacteria with mcr genes.…”
Section: Discussionmentioning
confidence: 88%
“…The plasmidmediated fosA3 gene variant is the most commonly reported in E. coli and other Enterobacteriaceae in Asia (Ito et al, 2017). Liu et al (2017) detected the fosA3 gene in seven ESBL-producing E. coli strain carrying the mcr-1 gene that were isolated from food of animal origin. The occurrence of fosfomycin resistance in Asia, but also its sporadic detection in strain of animal origin in Europe , represents another public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…We identified two strains (E29 and E36) that carried mcr-1 , fosA3 , and bla CTX-M-9 genes from river samples (Table 3). The mcr-1 , fosA3 , and ESBLs genes were previously identified in E. coli isolated from animal and food samples (Liu X. et al, 2017; Lupo et al, 2018), and the presence of these multidrug-resistant strains in urban river may present a serious threat to public health.…”
Section: Resultsmentioning
confidence: 99%